The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1177/0300060513515437
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine versus midazolam for sedation in upper gastrointestinal endoscopy

Abstract: Objectives: To investigate the efficacy and safety of sedation with dexmedetomidine in upper gastrointestinal endoscopy. Methods: Patients with ASA physical status I-II undergoing elective upper gastrointestinal endoscopy were randomly allocated to receive dexmedetomidine or midazolam for conscious sedation. Continuous peripheral oxygen saturation (SpO 2 ), heart rate, mean arterial pressure (MAP), Ramsay Sedation Scale (RSS) and numeric rating scale pain scores were recorded before, during and after the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 31 publications
1
37
0
2
Order By: Relevance
“…A further six studies were then excluded because of a lack of control groups ( n = 2), comparison of dexmedetomidine with propofol ( n = 2), and comparison of dexmedetomidine with placebo ( n = 2) . Finally, nine studies were included in the systematic review and meta‐analysis . The characteristics of these studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further six studies were then excluded because of a lack of control groups ( n = 2), comparison of dexmedetomidine with propofol ( n = 2), and comparison of dexmedetomidine with placebo ( n = 2) . Finally, nine studies were included in the systematic review and meta‐analysis . The characteristics of these studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The study by Wu et al . had potential bias in selective reporting and other aspects because it was a retrospective randomized study …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is correlated with cooperative sedation, which is different from the clouding of consciousness that occurs with drugs that act on GABA receptors, such as propofol or midazolam [17]. In a previous study, dexmedetomidine showed better oxygen saturation and RSS than midazolam [18]. In the present study, dexmedetomidine provided sufficient sedation (0 vs 83.6 ± 40.4 vs 89.9 ± 42.7 min), and the duration did not differ between the D-0.5 and D-1 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier randomized controlled trials evaluating the use of dexmedetomidine alone during small diagnostic and therapeutic procedures showed promising results. However, a potential disadvantage of dexmedetomidine is its hemodynamic side effects, which include hypotension and bradycardia …”
Section: Introductionmentioning
confidence: 99%